The Influence of Land Value Zone Changes and Selling Value of Building Tax Objects on Land and Rural and Urban Tax Revenue in Sambas Regency - B2051132011, ADY SUPRATNO (Jurnal Ekonomi Daerah (JEDA), 2019)
The aim of rearch is to find out and analyze the effect of land price increases and building prices on PBB-P2 tax revenue in Sambas Regency. Â The methodology of research is a quantitative descriptive analysis method with used multiple regression analysis with a panel data, the data used is secondary data sourced from the Sambas District Financial Agency Â for 2010-2016 year/period. Based on the results of statistical tests simultaneously (Test F) and partial (t test) all each tested variables (Land Value Zone and Building Tax Object Selling Value) have a significant and positive effect on the realization of the acceptance of Land and Urban and Urban Building Taxes in Sambas Regency.Keyword is Realization of Land and Rural and Urban Tax Revenues, Land Value Zones and Building Tax Object Selling Value.